2000
DOI: 10.1055/s-2000-8529
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of pioglitazone

Abstract: Pioglitazone HCl, a new thiazolidinedione (TZD), has been developed for the treatment of type 2 diabetes. The drug was tested in several trials that included over 5,000 subjects. Of these, over 3,500 subjects received active treatment. At doses between 15±45 mg pioglitazone was well tolerated with dropouts due to adverse events being similar in pioglitazone and placebo groups. The main side effect of treatment was mild to moderate peripheral oedema. Oedema was not associated with signs or symptoms of congestiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
(21 reference statements)
4
22
0
1
Order By: Relevance
“…88 Also, on a longterm basis the TZDs seem to promote weight gain ( Figure 6). Long-term treatment with Pioglitazone monotherapy is accompanied by substantial weight gain, 89 and this weight gain may likely be even higher when provided in combination with sulphonylureas or insulin, and it may be speculated whether this weight gain will increase with continuous treatment. The cause of the weight gain in humans is unclear, but is presumably because of increased fat deposition, the inherent mechanism of PPARg activation.…”
Section: Ppargamma Agonistsfadipogenic Treatment Of Type II Diabetes mentioning
confidence: 99%
“…88 Also, on a longterm basis the TZDs seem to promote weight gain ( Figure 6). Long-term treatment with Pioglitazone monotherapy is accompanied by substantial weight gain, 89 and this weight gain may likely be even higher when provided in combination with sulphonylureas or insulin, and it may be speculated whether this weight gain will increase with continuous treatment. The cause of the weight gain in humans is unclear, but is presumably because of increased fat deposition, the inherent mechanism of PPARg activation.…”
Section: Ppargamma Agonistsfadipogenic Treatment Of Type II Diabetes mentioning
confidence: 99%
“…If given along with a sulphonylurea or insulin, it often leads to severe hypoglycemia [22,23] . In view of this risk factor, its bioavailability is therapeutically crucial in view of possible pharmacokinetic drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…One published study review 76 found no change in patients on pioglitazone or placebo, but reported that diastolic blood pressure tended to show small decreases in those receiving pioglitazone, compared with placebo.…”
Section: Effect On Blood Pressurementioning
confidence: 99%
“…English translations of these papers are available from Takeda UK Ltd, although six of these are not readily available in the public domain. One full study report 62 and two review articles 63,76 relating to trials PNFP-010 and PNFP-027 are available in English.…”
Section: Number Of Studies Identifiedmentioning
confidence: 99%
See 1 more Smart Citation